PROSPECTS AND FURTHER OPPORTUNITIES FOR THE PROTECTION OF THE RIGHTS AND INTERESTS OF CITIZENS BY A CONSULAR INSTITUTION - Mirzayeva Muhayyo Dilshod qizi (Лучшие интеллектуальные исследования, 2023)
Several possibilities and avenues exist for improving consular institutions' role in safeguarding citizens' rights and interests. The scope of services offered by consular organizations can be broadened to meet the needs of nationals in need while traveling overseas. Assistance with legal representation, consular protection in times of crisis, and repatriation or evacuation are all part of this service. The use of digital innovation within consular institutions has the potential to enhance the quality of services provided by these organizations. Faster and more convenient passport services, visa applications, and emergency notifications are all possible thanks to online consular platforms, mobile applications, and digital communication channels.